Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
The Eastern Caribbean Currency Union (ECCU) countries' economies are heavily dependent on the United States for foreign direct investment, mainly in the tourism sector. The Selected Issues paper discusses economic development and policies of the ECCU. About one-third of the stayover tourists to the ECCU countries are from the United States., the top tourist-source country. The flow of remittances is also an important channel of influence, reflecting the significant proportion of Caribbean migrants living in the United States.